2011
DOI: 10.1016/j.limno.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Macroinvertebrate assemblages along a saline wetland in harsh environmental conditions from Central-West Argentina

Abstract: a b s t r a c tThe goal was to examine how macroinvertebrate taxonomic richness and density respond to spatialtemporal changes and to the influence of water physicochemical characteristics along the Bañ ado Carilauquen (BC). Benthic samplings were conducted seasonally and environmental parameters were recorded in five reaches of the BC. Cluster analysis was applied to compare taxonomic richness among sites. Community structure and spatial-temporal variation were explored using logarithmic regression. CCA was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
13
0
5
Order By: Relevance
“…Nevertheless, chiro nomids have be come adapted to these kinds of habitats (Lencioni & Rossaro 2005) and are one of the macroinvertebrate families most capable of surviving in such extreme environments (Lods-Crozet et al 2001). In the Mendoza River basin, during the melting season (summer), stressful environmental conditions caused by increments in suspended solids (Scheibler 2007) and river discharge (present study) were associated with low chironomid density. Our results confirm a negative correlation between discharge and chironomid density in summer.…”
Section: Prevalence Of Chironomids and Environmental Variablesmentioning
confidence: 55%
See 1 more Smart Citation
“…Nevertheless, chiro nomids have be come adapted to these kinds of habitats (Lencioni & Rossaro 2005) and are one of the macroinvertebrate families most capable of surviving in such extreme environments (Lods-Crozet et al 2001). In the Mendoza River basin, during the melting season (summer), stressful environmental conditions caused by increments in suspended solids (Scheibler 2007) and river discharge (present study) were associated with low chironomid density. Our results confirm a negative correlation between discharge and chironomid density in summer.…”
Section: Prevalence Of Chironomids and Environmental Variablesmentioning
confidence: 55%
“…Indeed, species richness in arid regions has been found to be notably low relative to areas with higher precipitation (Wright & Burgin 2010). Similar research on different aquatic environments in the Mendoza province has also reported low taxonomic richness (Scheibler 2007, Scheibler & Debandi 2008, Scheibler & Ciocco 2011.…”
Section: Prevalence Of Chironomids and Environmental Variablesmentioning
confidence: 75%
“…The influence of macrophytes on the composition and abundance of macroinvertebrate taxa is well known, since macrophytes contribute significantly to the habitat diversity (WIBERG-LARSEN et al, 2000;ROSI-MARSHALL and WALLACE, 2002). More specifically, macrophytes influence hydraulic roughness, water depth, flow velocity, and reduce predation, provide food and refuge and generate oxygenated environments (MILIŠA et al, 2006a;GOLUBIĆ et al, 2008;BAZZANTI et al, 2010;SCHEIBLER and CIOCCO, 2011). Water course size and slope gradient along streams have been shown to be good predictors of the distribution of caddis larvae and other macroinvertebrate assemblages (WIBERG-LARSEN et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the springs, the values of the diversity index were similar over the seasons, thus reflecting the more stable environmental conditions of these aquatic systems with respect to the saline lake during the year. A diminution in the number of species in those aquatic communities linked to high salinity had been noted by Peralta and Fuentes (2005) and Scheibler and Ciocco (2011) in their investigations performed exclusively at the Carilauquen spring. These last authors also included data on the hydrologic variability as a negative influence on the zoobenthic assemblages that they analyzed.…”
Section: The Zooplankton Communitymentioning
confidence: 58%
“…As stated above, the principal water source for the lake (and indeed for the entire basin) is from snowmelt during the spring, and mainly via the Malargüe River. The water of the springs and lake contains principally calcium sulfate and sodium chloride (Ostera and Dapeña 2003;Peralta and Fuentes 2005;Scheibler and Ciocco 2011). The high temperatures and scarce rainfall produce salt flats in the shallowest sections of the lake and on the southern and southeastern sides.…”
Section: Sampling Sitesmentioning
confidence: 99%